Multiple Dental Inclusion in Monozygotic Twins with Congenital Visual Impairment. (7th August 2020) - Galluccio, G.; Impellizzeri, A.; De Stefano, A. A.; Serritella, E.; Guercio Monaco, E.
Abstract : The study presents two monozygotic twins (MZ) with multiple impacted teeth, affecting the upper canines and lower second molars, as well as congenital aniridia. The clinical aspect of the upper canines is peculiar because of the different positions—palatal in one and buccal in the other twin. Studies reporting different scenarios of impaction in monozygotic twins can contribute more data to the debate on tooth eruption aetiology and more so in this case because of the association with a genetic panocular disease. Patients' Concerns . The patients were referred by a general dentist, who diagnosed the presence of multiple inclusions. Diagnostic Study . Both patients showed severe malocclusion, classified as grade 5 of the Index of Orthodontic Treatment Need (IOTN). The MZ showed class I malocclusion, upper and lower crowding, and impacted lower right and left second molars. A Dentascan was prescribed for the canine impaction. The impaction of the upper canine was palatal of 2.3 in one of the MZ and buccal of 1.3 in the other one. The same altered pattern of eruption of the lower second molars was identified in both twins. The proposed treatment plan contemplated orthodontic surgical recovery of the impacted elements, followed by orthodontic treatment with multibracket appliance after the extraction of the first four premolars, given the crowding entity. The use of a retraction spring action was chosen for the recovery of the lower second molars. Many aspects of the possible genetic aetiology of tooth impaction are still under discussion. The study of diseases in twins offers decisive information. Finally, the possibility that alterations in the eruptive pattern of the dental elements may be associated with other congenital problems broadens the range of investigations related to the possible aetiological causes of the inclusions in humans.